Completeness of follow up in a cohort study of mortality using the United Kingdom National Health Service Central Registers and records held by the Department of Social Security. - Darby, S; O'Hagan, J; Kendall, G; Doll, R; Fell, T; Muirhead, C (1991)
STUDY OBJECTIVE: The aim was to evaluate and improve the completeness of follow up in a cohort study of mortality carried out using the UK National Health Service (NHS) Central Registers. SETTING: This was a follow up study of UK servicemen who served abroad in the 1950s and 1960s, including those who participated in the UK atmospheric nuclear weapon tests and experimental programmes. DESIGN: Details of men for whom follow up achieved using the NHS Central Registers was unsatisfactory were submitted to the Department of Social Security (DSS) for tracing, as were details of men born before 1916 and reported by the NHS Central Registers as currently registered with a general practitioner, and a 1% sample of remaining men born in or after 1916. MEASUREMENTS AND MAIN RESULTS: The additional follow up increased the number of deaths fully identified in the cohort by 6.5%. Mortality among those untraced on the NHS Central Registers was substantially greater than in the cohort as a whole (10.2% v 6.9%). Among those reported by the NHS Central Registers as not currently registered with a general practitioner, 2.7% were found to have died, as were 1.1% of men born before 1916 and currently reported to be registered with a general practitioner. As expected there was clear evidence that information about emigrations supplied by both the NHS Central Registers and DSS is far from complete. CONCLUSION: Standardised mortality ratios based on follow up via the NHS Central Registers alone are likely to be somewhat low, and this should be borne in mind when interpreting the data.